2020
DOI: 10.1371/journal.pone.0242677
|View full text |Cite
|
Sign up to set email alerts
|

Structures of three MORN repeat proteins and a re-evaluation of the proposed lipid-binding properties of MORN repeats

Abstract: MORN (Membrane Occupation and Recognition Nexus) repeat proteins have a wide taxonomic distribution, being found in both prokaryotes and eukaryotes. Despite this ubiquity, they remain poorly characterised at both a structural and a functional level compared to other common repeats. In functional terms, they are often assumed to be lipid-binding modules that mediate membrane targeting. We addressed this putative activity by focusing on a protein composed solely of MORN repeats—Trypanosoma brucei MORN1. Surprisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 107 publications
(518 reference statements)
0
14
0
Order By: Relevance
“…A recent in vitro lipid-binding study of over 100 proteins of the protozoan ciliate Tetrahymena thermophila confirmed the lipid-binding capacity for similar 14-aa long MORN consensus motifs ( 80 ). In contrast, it appears that the negative surface charges on the parasite MORN domains exclude a phospholipid-binding function, both rather mediate binding to specific cytoskeletal protein domains ( 81 ). However, both parasitic and mammalian MORN domain structures are capable of binding specific cytoskeletal protein domains as discussed in sect.…”
Section: Junctophilin Biogenesis and Molecular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent in vitro lipid-binding study of over 100 proteins of the protozoan ciliate Tetrahymena thermophila confirmed the lipid-binding capacity for similar 14-aa long MORN consensus motifs ( 80 ). In contrast, it appears that the negative surface charges on the parasite MORN domains exclude a phospholipid-binding function, both rather mediate binding to specific cytoskeletal protein domains ( 81 ). However, both parasitic and mammalian MORN domain structures are capable of binding specific cytoskeletal protein domains as discussed in sect.…”
Section: Junctophilin Biogenesis and Molecular Functionsmentioning
confidence: 99%
“…However, both parasitic and mammalian MORN domain structures are capable of binding specific cytoskeletal protein domains as discussed in sect. 2.2.3 ( 81 ).…”
Section: Junctophilin Biogenesis and Molecular Functionsmentioning
confidence: 99%
“…This particular organization allows the junctophilins to link the ER membrane and the plasma membrane to one another. The MORN motifs are known to bind to the internal leaflet of the plasma membrane and specifically to phosphatidylinositol phosphate species [ 29 , 30 , 31 ], although the role of the MORN motif as a bona fide membrane-binding domain has been recently called into question after the observation that a number of proteins that also contain MORN repeats are either not associated with membranes or employ alternative domains to anchor to the membrane, or utilize their MORN motifs as protein-protein–protein interaction domains rather than membrane association domains [ 32 , 33 , 34 ]. Therefore, the ability of the MORN motifs in the junctophilins to associate with the membrane might arise from the presence of positively charged residues in the less conserved regions or from post-transcriptional modifications.…”
Section: The Junctophilin Familymentioning
confidence: 99%
“…It is generally assumed that MORN repeats bind to lipids and are responsible for plasma membrane targeting. However, there is a growing volume of evidence suggesting that MORN repeats may mediate protein-protein interactions [ 24 , 25 ]. Indeed, by using a GST-pull-down assay coupled with mass spectrometry, we have demonstrated that MORN repeats are responsible for the majority of SET7/9 interactions [ 10 ].…”
Section: The Structural Organization Of Set7/9 Methyltransferasementioning
confidence: 99%